Fundamentos filosóficos, políticos e educativos da polícia: da sensação de segurança à instituição policial - Leal, Gabriel Rodrigues (2015)
This work aims to support the police science analyzing, first, the affection "sense of security" through a structured ontology in triangulation between the "moral failure" in Pascal, the "science of affection" in Espinosa and the "instinct death "in Freud:" ontology of the abyss. " Given this initial ontoantropológica construction, held the book I will trace a brief genealogy of the police institution in Book II now accosted in stud procedure Nietzsche and documentary research on the history of security institutions, or rather, the security-military thinking , greatly Brazilian army. It is, in Book II, therefore, to follow the history of these institutions and their adherence or not to book ontology I. In Book III, in turn, began to investigate the police-military education and general lines an understanding of police-military educational process to give scope to the idea of a precise scientific object or set to public safety sciences, then described in Book IV. Therefore, a sequence of arguments juxtaposition we rely, first, in the ontology; later, in the institutional history of military thought followed by their educational practice scoped to the object "security," to bring in the book IV, an introductory proposal of "public safety sciences," trying to understand their epistemological foundations founded on epistemology Virtue Ernst Sosa (2013) and also moral, established and reading in orthopraxis military values. In short, it is investigating the possibility of understanding security, and its structural affection for the man, as an object of knowledge of police institutions with scientific status, which is founded first and foremost, the year of the first science, philosophy and its offer of elucidating the problem of evil cogent to man and consequently the whole social body, read, since the front pages through an analysis of Hobbes. It is based, in general, still, reading the police not only as reassuring institution and guarantee rights in democracy, insist as public policies, but also as the ultimate repository of cohesion and social peace through the systematic use of violence to "subject Hobbesian "to preserve order, the foundation of social coexistence possible